2021
DOI: 10.1111/cen.14412
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the variation across 6741 family/general practices in England in the use of treatments for hypogonadism

Abstract: Introduction We have previously reported rates of diagnosis of male hypogonadism in United Kingdom (UK) general practices. We aimed to identify factors associated with testosterone prescribing in UK general practice. Methods We determined for 6741 general practices in England, the level of testosterone prescribing in men and the relation between volume of testosterone prescribing and (1) demographic characteristics of the practice, (2) % patients with specific comorbidities and (3) national GP patient survey r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…As expected, pituitary disease, testicular cancer and undescended testes were more prevalent in men prescribed TRT versus men not prescribed TRT. 7,14 However, contrary to a recent study in primary care, 10 IHD, DVT/PE and stroke were associated with a higher likelihood of prescribing TRT in our cohort. This may suggest that men with CV comorbidities are more likely to have hypogonadism.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…As expected, pituitary disease, testicular cancer and undescended testes were more prevalent in men prescribed TRT versus men not prescribed TRT. 7,14 However, contrary to a recent study in primary care, 10 IHD, DVT/PE and stroke were associated with a higher likelihood of prescribing TRT in our cohort. This may suggest that men with CV comorbidities are more likely to have hypogonadism.…”
Section: Discussioncontrasting
confidence: 98%
“…2 A recent UK study reported that variation in testosterone prescribing across 6741 general practices is related to unidentified factors such as GP choice/preference. 10 A study using semi-structured interviews with clinicians concluded that diagnostic ambiguity of age-related hypogonadism and beliefs about the appropriateness of TRT influenced testosterone prescriptions in men. 21 Similarly, other studies have reported system-level factors We observed that men between the ages of 45-69 years were most likely to be prescribed TRT compared to other ages (highest age group 50-54 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used published data to identify the four most prescribed testosterone formulations and annualised dosing in the UK to define the percentage of men prescribed testosterone using each formulation 22 : testosterone 16.2 mg/g gel (Testogel), 29%; testosterone 2% gel (Tostran), 15%; combined testosterone esters (Sustanon 250), 8%; testosterone undecanoate 1 g (Nebido), 46%. British National Formulary and the NHS indicative prices were used to value these medicines (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…1 Studies investigating the underlying reasons for generalist physician prescribing of testosterone are important to guide future clinical practice. 6 Heald et al 7 analysed data from a variety of data sources to examine factors associated with testosterone prescribing for over 6000 GP practices within England. They also provide important data on changes in formulations of testosterone prescribed over recent years; injectable forms of testosterone are becoming relatively more common, and transdermal testosterone now mostly administered using a pump-dispenser rather than sachet.…”
mentioning
confidence: 99%